Integration of Design Geometry with “Computational Making” in Basic Design Studio A Case Study of Lanterns Project - Gündüz, G.; Oral, H.; Yazar, T. (Education and research in Computer Aided Architectural Design in Europe, 2018)
Basic design education, as an introduction of design principles to novice students, has two-way of teaching which are design thinking and professional training, since Bauhaus. Initiated in 2009, the Computation-based Basic Design Studio creates a common ground through discussions between students, academics, and professionals from various backgrounds. In this paper, the implementation of parallel courses named Computation-based Basic Design Studio and Design Geometry is discussed upon final assignment of the first semester-New Year's Lanterns. The given assignment structured as a cyclic process through constant feedback between geometric relations, material performance, and, joinery details to achieve novel outcomes that exceed the preliminarily set structural criteria. In relation to individual processes and outcomes of the final assignment, observed tendencies developed by students', at the end of their first-term in design education, will be discussed as final remarks. © 2018.
36th International Conference on Education and Research in Computer Aided Architectural Design in Europe, eCAADe 2018 -- 19 September 2018 through 21 September 2018 -- -- 275769
Keywords: Basic Design; Design Education; Design Geometry; Polyhedra